Iran’s policy in the Caspian region at the present stage: results and prospects - Vahid Hosseinzadeh (Проблемы постсоветского пространства, 2017)
One of the most important players in the geopolitical process in the Caspian region is Iran. In this article, we consider Iran’s policy on a wide range of problems in the Caspian Sea region that the country has been following since the collapse of the Soviet Union. For more than two decades, one of the important tasks of the Iranian Foreign Ministry was to deﬁne the international legal regime of the Caspian Sea, which was complicated by the geopolitical changes in the region associated with the collapse of the Soviet Union and the emergence of new Caspian states - Turkmenistan, Azerbaijan and Kazakhstan. Initially, Iran tried to justify the division of the sea, based on the former Soviet-Iranian agreements. However, the new Caspian states believed that the geopolitical status underwent fundamental changes and the previous contracts couldn’t justify modern challenges. In this connection, the tasks of preserving the national interest to the maximum extent and at the same time maintaining constructive relations with other Caspian states, especially with the Russian Federation, became urgent for Iran’s policy. Environmental pollution and lack of ﬁnancial and technological resources for energy extraction are a serious problem for Iran in the Caspian Sea. The Islamic Republic of Iran is still at the stage of research into the extraction of energy resources in the region and has not entered the mass production stage due to international sanctions. However, after the agreement with the “5+1” and the lifting of sanctions, Iran has the opportunity to extract oil and gas from the Caspian. The activities of Western companies and their close cooperation with the new Caspian states are also a problem for Iran. The military presence of the West, especially the United States, in the Caspian region is considered a direct security threat from the Iranian point of view, and Iran has serious objections and fears in this regard.